Comparison of Intraperitoneal Instillation of Bupivacaine and Bupivacaine with Dexmedetomidine for Postoperative Analgesia after Laparoscopic Surgery - Dr. Namrata, Dr. Hiteshkumar S. Patel, Dr. Nilesh Solanki, Dr. Bharat Shah (International Journal of Innovative Research in Medical Science, 2016)
Background and aims: Post-operative pain is one of the major problems in laparoscopic surgeries, wherein lack of control on it has many side-effects such as tachycardia, hypertension, myocardial ischemia, decreased alveolar ventilation, and prolongs hospital stay. We have evaluated the antinociceptive effects of intraperitoneal instillation of bupivacaine plain and bupivacaine with dexmedetomidine in patients undergoing laparoscopic surgeries. Materials: A total of 100 patients belonging to American Society of Anesthesiologist physical status I-II, in the age group of 18-70 years, of either sex undergoing laparoscopic surgery under general anesthesia were divided in two groups. Group B received bupivacaine (0.25%) 40 ml intraperitoneal instillation and group BD received bupivacaine (0.25%) 40 ml with dexmedetomidine 1μg/kg intraperitoneal instillation before removal of trocar at the end of surgery. The quality of analgesia was assessed by visual analogue scale (VAS) and sedation by Ramsey sedation score. Time to first request of analgesia, total dose of analgesic in first 24 hrs and adverse effects were also noted. Results: There was statistically significant difference in VAS at six hours after surgery in group BD (3.14±0.40) compared to group B (4.12±0.82) up to 24 hours with higher sedation score for first six hours. The time to first rescue analgesic was significantly higher in group BD (7.76 hours) compared to group B (5.92 hours) and less total analgesic consumption(mg) in group BD (1.9) compared to group B (2.21). Conclusion: Intraperitoneal instillation of bupivacaine with dexmedetomidine significantly prolong the duration of analgesia as compared to intraperitoneal instillation of bupivacaine alone without any side effects.